Matlamat Perintah Khidmat Masyarakat di Mahkamah Syariah Menurut Maqasid Syariah dan Pandangan Hakim Syarie - Nurbazla Ismail; Mohd Al Adib Samuri (Universiti Sains Islam Malaysia, 2024)
Punishment in Islam should meet the main objectives of sentencing based on Islamic law. As a community service order is a new sentence to the criminal justice system proposed in Sharia, the penalty is a need to ensure conformity with Islamic law which is in accordance with the Maqasid shariah. However for the purpose of implementation will have to consider the views of certain groups. Thus, this study was conducted to examine the sentence of community service orders in accordance with Maqasid Shariah. In addition, this study also aims to identify the goals of this execution in the view of Judge.